THE IMPLEMENTATION OF TEAM BASED LEARNING TO ENHANCE STUDENTS’ LEARNING MOTIVATION - Hafis, Maliqul (IKIP PGRI Pontianak, 2016)
Team Based Learning (TBL) is a teaching strategy where students work together in small groups on a structured activity and it is presumably able to enhance students’ learning motivation and learning outcome. The data of this study were collected by using questionnaire, observation, interview and diary which used successively. Descriptive statistic and constant comparative method were used to analyze the data.The data analysis revealed that (1) TBL can enhance students’ learning motivation (2) Difficulties of TBL when it was applied in enhancing students’ learning motivation.The results of this study implies that TBL is strongly eligible to be implemented to enhance students learning motivation at class 9D Junior High School at Sragen, Central Java. As some difficulties are found in implementing TBL to improve students’ learning motivation, it is important for the teachers to be able to identify the problems that they are facing while implementing TBL by referring to previous study, discussing with the other teachers asking directly to students what they are feeling when TBL was implementing.Keywords:Team Based Learning, Students’ Learning Motivation.